PERENCANAAN PENDIDIKAN DALAM BINGKAI MANAJEMEN PENDIDIKAN ISLAM - Alfa, Dwi Suryani; Fitria, Eliga; Asmendri, Asmendri; Sari, Milya (LPPM UM Metro, 2025)
Planning is the first and most crucial stage in educational management. Planning is crucial to the entire management process. In education, planning serves not only as a technical guideline but also as a moral and spiritual responsibility in realizing educational goals based on Islamic values. This article aims to analyze the concept of planning, the urgency, and the relevance of educational planning in the context of Islamic educational management, reviewed from the perspective of planning theory and management from an Islamic perspective. The method used is a literature review through relevant primary and secondary sources. Based on the results of the discussion, it is clear that educational planning plays a crucial role in ensuring that educational institutions' activities are more focused, measurable, effective, and efficient. This is in accordance with the Islamic perspective, which is reflected in the planning principles of trust, ihsan, and ikhtiar, as conveyed in the Qur'an (Al-Hasyr: 18 and Al-Anfal: 60). Good planning will have a positive impact on improving the quality of education. Therefore, the key to the success of Islamic educational institutions is to integrate modern management principles and Islamic values.